(untitled) (Journal of the College of Education for Women, 2019)
The research aimed at revealing the relation between Independency and TheConcept of self of The Children Who have Working and not Working Mothers,and to accomplish the aim of the research, the researcher built two measures, thefirst was to measure Independency and the second was to measure Concept of self. after Appling them on the sample of the research which consists of Children(males and females ) Working and not Working Mothers . the following resultappeared : The difference in the degrees of independency was in favor of the maleswho have working mothers and the females who have not Working Mothers . The difference in the degrees of Concept of self was in favor of the maleswho have working and not Working Mothers . There is a statistical function relation between the degrees of Independencyand The Concept of self of The males Who have Working Mothers. There is a statistical function relation between the degrees of Independencyand The Concept of self of The females Who have Working Mothers.The researcher reaommended the importance of enlightening the Mothers aboutthe importance of and encouraging their children about their independency anddepending on themselves and realize their selves and understanding them and shesuggested many studies in this field.